A multilayer approach for systemic risk in the insurance sector. (September 2022) - Clemente, Gian Paolo; Cornaro, Alessandra
Abstract: In this paper, we provide a methodology suitable to identify relevant insurance companies in a systemic risk framework. To this end, we propose a complex network approach where insurers are linked to form a global interconnected system. In particular, we extend the current literature proposing an approach based on a directed weighted multilayer network. The reciprocal influence between insurers is indeed considered in each period and in subsequent periods, calibrating arc weights on the basis of specific risk measures. Hub and authority scores are then used to assess the prominence of a company in spreading and receiving risk from the others. Highlights: We identify relevant insurance companies in a systemic risk framework. Insurers are linked in a global interconnected system described by complex networks. We extend existing approaches using a directed and weighted multilayer network. Insurers are selected extending the concept of hub and authority scores. We provide marginal and conditional centralities indicators.